Case study of stamping process in producing Perodua Kancil's door / Isfanizam Ismail and Shahrin Jaminan - Ismail, Isfanizam; Jaminan, Shahrin
A case study on the stamping process involving the production of Perodua Kancil's door done at Ingress Technologies Sdn. Bhd., a Perodua's vendor located at Bukit Beruntung, Rawang. Actual sheet metal operation or stamping process has many underlying elements to support a successful operation. These elements are crucial in the production and are discussed throughout the report. They are die engineering, equipments, actual stamping process, problem and countermeasure. Die engineering are first to be studied as they hold the utmost important in stamping. This includes die construction, die maintenance system, and die design. To support die engineering, equipments used in stamping line are discussed. They are micro shear machine, fully automated tandem press line, and robots. Later, the actual stamping processes which include drawing, trimming, piercing, and flanging are studied along with their raw materials and products. In addition, the products are discussed further in term of their materials and finish parts. Like any other processes, there are defects and problems to be solved. Burr, galling and pimples are among the defects encountered and their countermeasure are also studied. To increase efficiency, preventive countermeasures are applied during the case study. For example schedule maintenance, performance indicator incorporate with production planning control. In conclusion stamping processes are very nimble and sensitive to the surrounding. However it provide the edge for the manufacturing of automotive parts.